PELAKSANAAN PERJANJIAN KERJASAMA ANTARA PT. SEPATU BATA TBK DAN PENGECER SEPATU BATA KOTA PAYAKUMBUH - Mia Rosdiana; Rika Lestari; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The agreement cooperation PT. Sepatu Bata Tbk and retails shoes Bata happen because the parties company requires retailers to channel his factory in form of shoes, bags, sandals and sock up to consumer. The company requires a retailers to outlets. The relationship retailers and the company is agreement cooperation. The implementation of the agreement did not happen well. There was disagreement happened in the implementation of the agreement. The porpose or writing this, the thesis: First, The implementation of the agreemant cooperation between PT. Sepatu Bata Tbk and retailers shoes Bata in the city Payakumbuh. Second, Barriers in practice of the agreemant cooperation between PT. Sepatu Bata Tbk and retailers shoes Bata in the city Payakumbuh. The basis of legal used in the discussion of this is the book to III BW (Burgelijk Wetbook) about agreement.The kind of this study is the research legal sosiologis. The study was conducted in the city Payakumbuh outlets the shoes Bata on the road Ahmad Yani BB1 No 4 Market tenement Payakumbuh, the county Fifty the City , West Sumatera. Populas and samples in this study is retailers shoes Bata Payakumbuh and representatives of the company of PT. Sepatu Bata Tbk authorities to the city Payakumbuh.The results of the study authors concluded, the implementation of the agreemant cooperation between PT. Sepatu Bata Tbk and retailers shoes Bata not happen well, this is evident from : First, The wanprestasi done by the like : raise a retail price of goods, reduce the sales clerk, undermining the label, late sent of goods to the store . Second, The barriers like : the delay delivery of goods to the shop, limited goods a new model, the sales of income not reaching the target. Advice from the author : The first for retails shoes Bata to study and understand the contents of the first to prevent the dispute later in the day, for the parties respecting the right and the obligation to each of the well. Second to establish good communication, because cooperation need good communication that happen in the accordance hope the party so that the obstacles in the unavoidable.Keywords : The Cooperation - PT. Sepatu Bata Tbk – Wanprestasi